Public interest and engagement in care for brain health in Slovenia: the role of education - Perovnik, Matej; Kos, Hana; Vidmar, Gaj; Fabjan, Sara; Hawlina, Hana; Tomat, Nastja; Trol, Dolores; Bresjanac, Mara (Frontiers in Public Health, 2025)
Background and objectiveKnowledge gap theory posits that individuals with better education have better opportunities to obtain, understand and utilise available information. In a health-related context, this insight could lead to a more effective disease prevention. The aim of our study was to test the hypothesis that knowledge gap underlies differences in behaviour aimed at maintaining brain health.MethodsWe conducted an online survey investigating Slovenian public view on brain, brain research, and science-based recommendations for brain health. The survey was filled out by a total of 2,568 respondents, of whom 2,450 completed it in full. They were divided into two subgroups based on their self-reported brain-related education, i.e., the lay subgroup (n = 1,012) and a topically educated group (n = 1,438), i.e., the educated subgroup. Among the latter, 728 participants reported to have a Bachelor’s degree or higher education. We analysed the views of this sample subgroup on brain, neuroscience, and science-based brain health recommendations, and compared them with age- and education-matched lay subgroup (n = 565) from the same survey.ResultsEducated individuals showed greater awareness and adherence to science-based recommendations compared to the lay respondents, specifically in the perceived importance of following a healthy diet, exercising, ensuring time for rest, relaxation and maintenance of social contacts, acquiring new knowledge and skills and using supplements that are considered to improve mental abilities (all p < 0.005), but not in the perceived importance of getting enough sleep, avoiding drugs and alcohol or injuries and performing mentally-challenging activities or cognitive training (all p > 0.10). Educated individuals more frequently reported following a healthy diet, engaging in physical activity and socialising, acquiring new knowledge and skills, performing mental challenges and cognitive training, and using supplements (all p < 0.005), but not getting sufficient sleep, avoiding drugs, alcohol or injury, or ensuring time for rest and relaxation (all p > 0.08). A larger proportion of lay than educated participants (32 and 17%, respectively) identified lack of information as a reason for not engaging in healthy practices (p < 0.001). Educated participants outperformed lay individuals in identifying diseases amenable to lifestyle modification.ConclusionUnderstanding the differences in brain health perceptions between educated and lay individuals is crucial for developing effective public health strategies. Our results highlight a substantial knowledge gap in the Slovenian population and the need for targeted educational interventions that account for varying degrees of knowledge in different population segments which could lead to better adherence to healthy lifestyle practices.